ANTIBODY IgG LEVELS AND ADVERSE EVENTS FOLLOWING IMMUNIZATION AFTER THIRD DOSE OF MODERNA VACCINE IN HEALTHWORKERS AFTER TWO DOSES OF SINOVAC VACCINE - Ade Tiur Rumondang; Utari Hartati Suryani; Debie Rizqoh; Mardhatillah Sariyanti; Besly Sinuhaji (JURNAL KEDOKTERAN DAN KESEHATAN, 2023)
Health Care Workers (HCWs) are a top priority to receive the vaccination for Coronavirus Disease 2019 (Covid-19). After two doses of the Sinovac vaccine as the primary vaccine, protection against Covid-19 weakens over time, so a booster vaccination is considered to produce more antibodies. In addition, each vaccine is inseparable from Adverse Event Following Immunization (AEFI). This study compares antibody levels and AEFIs between two doses of the Sinovac vaccine with the Moderna booster. This research is an observational analytic study with a cross-sectional study design and the sampling method is random sampling with a total of 74 HCWs using a consecutive sampling method. Samples that had received two doses of the Sinovac vaccine or booster doses of the Moderna vaccine after two doses of the Sinovac vaccine were included. Samples that had been infected with Covid-19 before vaccination were excluded. IgG antibody levels were measured using Chemiluminescent Microparticle Immunoassay (CMIA), while vaccine type and AEFI were gathered via questionnaire. The severity of AEFIs is based on WHO classification. The data analysis used the Mann-Whitney and Chi-Square tests with a 95% Confidence Interval (CI) to determine the relationship between variables. Twenty-nine subjects received two doses of the Sinovac primary vaccine (38.2%), and forty-five received the Moderna booster vaccine (59.2%). In booster doses of the Moderna vaccine recipients, antibodies tended to be higher, and the most common AEFIs were systemic. There was a significant difference in IgG antibody levels between recipients of two doses of the Sinovac vaccine (median=2888.8 AU/mL) and booster Moderna vaccine recipients (median=18081.04 AU/mL) (p=0.000, p <0.05). There were significant differences in AEFI in the groups receiving two doses of the Sinovac vaccine and those receiving the booster vaccine (p=0.000, p<0.05). This study concludes that there is a significant correlation between administering the Covid-19 vaccine and post-vaccination IgG antibody levels and AEFI.